THE EFFECT OF RETURN ON ASSETS AND PRICE BOOK VALUE ON INVESTMENT OPPORTUNITY SETS AND THEIR CONSEQUENCES ON LEVERAGE AND EQUITY (Study on Manufacturing Companies Listed on the IDX for the 2019-2021 Period) - Lia Puji Lestari; Taswan Taswan (SEAN Institute, 2023)
This study aims to analyze the effect of Return On Assets and Price Book Value on Investment Opportunity Set and the consequences for leverage and equity in manufacturing companies listed on the Indonesia Stock Exchange in 2019-2021. The study focused on manufacturing companies listed in Indonesia Stock Exchange during 2019-2021. The type of data used is secondary data. Sampling method used purposive sampling with 250 data from 86 manufacturing company listed in IDX. Data analysis using multiple Linear Regression with Descriptive Analysis, Classic Assumtion and Hipothesis Test. The result of the study show that Return On Assets has positive and significant effect on Investment Opportunity Set. Price Book Value has not significant effect on Investment Opportunity Set. Return On Assets has negative and significant effect on Leverage. Price Book Value has not significant effect on Leverage. Investment Opportunity Set has positive and significant effect on Leverage. Return On Assets has positive and significant effect on Equity. Price Book Value has negative and significant effect on Equity. Investment Opportunity Set has not significant effect on Equity.